General practitioner-centered rural obesity management: Design, protocol and baseline data of the German HAPpEN pragmatic trial - Haderer, Marika; Hofmann, Reiner; Bartelmeß, Tina; König, Laura; Betz, Constanze; Al Masri, Mirna; Bader, Alisa; von Schau, Natascha (Preventive Medicine Reports, 2025)
Objective: HAPpEN aims to implement and evaluate a holistic general practitioner-centered, interdisciplinary obesity management strategy in rural Germany, focusing on feasibility, health outcomes, and economic benefits. Methods: HAPpEN is a 12-month, pragmatic single-arm, multicenter trial, informed by a formative survey, and initiated in April 2023 with 98 obese participants (body mass index, BMI ≥ 30 kg/m2) in Kulmbach, Germany. The program integrates nutritional counseling, physical activity, and behavior change techniques, including smartphone-based self-monitoring. Monthly consultations help set personalized goals using a multi-stage grading scale. Primary outcomes include BMI, body weight, waist circumference, heart rate, blood pressure and parameters, while secondary outcomes assess quality of life, wellbeing, health literacy, social interaction, and digital therapy support. Results: The baseline cohort (mean age: 46.9 ± 11.8 years, 74.1 % female) exhibited high obesity rates (mean BMI: 40.1 ± 6.1 kg/m2), with 48.5 % classified as grade III obese. Common comorbidities were hypertension (51.8 %), dyslipidemia (30.5 %) and diabetes (21.8 %). Chronic joint paint, mainly in the knees and hips, affected up to 82.4 %. A familial aggregation of obesity, diabetes, and cardiovascular diseases was noted, alongside behavioral challenges such as lack of physical activity (81.8 %) and unhealthy eating habits (56.8 %). Conclusion: HAPpEN addresses obesity's multifactorial nature through general practitioner-led, community-based, and digital strategies to promote sustainable lifestyle changes in rural areas. The trial aims to inform primary care obesity management guidelines, focusing on improving health literacy, patient engagement, and long-term clinical benefits. German Clinical Trials Register: DRKS00033916.
CRIS-Team Scopus Importer:2025-01-31
Keywords: eHealth; Obesity; Pragmatic trial; Primary health care; Rural; Social support